Effects of organic fertilizers and tillage on yield and its components of three varieties of Corchorus olitorius L. produced in South Benin - Manhognon, Faton Oscar Euloge; Bonou-Gbo, Zaki; Azonwakin Rodrigue, Akotegnon; Hambada Koffi David, Montcho; Ogoubiyi Tounde, Chakour-Ola; Djedatin, Gustave; Atindehou, Cynthia; Gandonou Gbossegnon, Bernard Christophe; Gnancadja-Andre, Léopold Simplice; Aléodjrodo, Edorh Patrick (European Scientific Journal, ESJ, 2025)
The intensive use of chemicals is depleting the soil in Benin, limiting crop yields in general, but in particular vegetable crops and more specifically Corchorus olitorius. This study aims to evaluate the influence of organic fertilizer and tillage on the agro-morphological characteristics of three varieties of corete. A split plot device in 02 repetitions, the main factor of which is the dose of organic fertilizer at 08 levels, was installed at two different sites, one of which is frequently plowed and the other of which has not been exploited during the last 5 years. The data collected during the trial were entered and processed in the Excel 2016 spreadsheet and subjected to various analyses including descriptive statistics, and analysis of variance with the Statitica software. The principal component analysis was performed with R 4.2.1 software and identified characters that are controlled by the treatments applied. The performance of the different varieties was assessed in the different study environments. The results show that soil amendment with varying doses of organic fertilizers associated with soil types improves the agro-morphological parameters of the plant. This combination makes the nutrients available. Thus, organic fertilizer is a significant fertilizer capable of improving soil fertility. The use of organic fertilizers contributes to the improvement of soil status and crop yields through organic fertilization.